2020
DOI: 10.1039/c9ay01690b
|View full text |Cite
|
Sign up to set email alerts
|

Generating linear oxygen gradients across 3D cell cultures with block-layered oxygen controlled chips (BLOCCs)

Abstract: BLOCCs are readily assembled structures of laser cut acrylic and silicone, capable of imposing physiologically relevant oxygen gradients across 3D cell cultures. With sensors and cell-based readouts, we quantified cell-microenvironment relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Although there have been major efforts in developing methods to control and measure the oxygen tension in microfluidic devices, as discussed in the previous sections, usually these devices have only been validated by confirming well-known biological or pathological processes affected by oxygen levels, as an understandable first proof-of-concept step. Nevertheless, several studies have already provided interesting insights, e.g., with respect to the relation between oxygen levels and cell migration, 82,87,[93][94][95][96][97][114][115][116] ROS production, 74,[117][118][119] activity of HIFs 88,120,121 and metabolic changes. 77,79,122,123 Other work has focused on intermittent vs. chronic hypoxia 81,83,87,124 or investigated targeting of hypoxia by hypoxia-responsive drugs.…”
Section: Biological Applications Of Hypoxia In Microfluidic Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there have been major efforts in developing methods to control and measure the oxygen tension in microfluidic devices, as discussed in the previous sections, usually these devices have only been validated by confirming well-known biological or pathological processes affected by oxygen levels, as an understandable first proof-of-concept step. Nevertheless, several studies have already provided interesting insights, e.g., with respect to the relation between oxygen levels and cell migration, 82,87,[93][94][95][96][97][114][115][116] ROS production, 74,[117][118][119] activity of HIFs 88,120,121 and metabolic changes. 77,79,122,123 Other work has focused on intermittent vs. chronic hypoxia 81,83,87,124 or investigated targeting of hypoxia by hypoxia-responsive drugs.…”
Section: Biological Applications Of Hypoxia In Microfluidic Devicesmentioning
confidence: 99%
“…Specifically, the device was stratified in four areas based on the oxygen tension, and in areas of the device where the oxygen tension was below 27 mmHg O 2 (∼3.5% O 2 ) a higher oxidative stress was found that was associated with a greater hypoxic response, which was not the case in devices not exposed to an oxygen gradient, where the eGFP intensity did not change significantly. 120 Rexius-Hall et al investigated the cellular response of human lung microvascular endothelial cells to oxygen tension in real-time using an open-well configuration equipped with two meandering gas channels below (device depicted in Fig. 3E top).…”
Section: Activity Of Hifs and Hypoxia-triggered Metabolic Changesmentioning
confidence: 99%
“…In particular, this chip was designed to have cell-containing chambers in the center between two lateral parallel channels, where oxygenated and deoxygenated gas mixtures were flowed to impose physio-pathologically-relevant O 2 gradients in the cell-seeded regions. O 2 gradients and resulting cellular responses were simultaneously mapped in real-time to examine whether these cells modify their activity proportionally to O 2 tensions [162].…”
Section: Optical Biosensorsmentioning
confidence: 99%
“…Fibroblast migration increased when myocytes were exposed to higher levels of ischemia (generated through taller stacks) and was reduced in the absence of cardiac myocytes or with the pharmacological inhibition of TGF-β ( 27 ). Other methods have been developed that similarly modify hydrogels to generate oxygen gradients ( 67 ) by using oxygen-consuming enzymes during hydrogel cross-linking ( 68 , 69 ), embedding a hydrogel between gas flow channels ( 70 ), or linearly increasing cell density and thus oxygen consumption rates ( 71 ), but these methods have not yet been implemented to model post-infarct myocardium.…”
Section: In Vitro Models Of Myocardial Ischemia and Hypoxiamentioning
confidence: 99%